Optimalisasi Program Mengajar Al-Qur'an Dengan Metode Qurani Pada Lembaga Pemasyarakatan Narkotika Pakem Yogyakarta - Rifaatul Indana (https://journal.metanusantara.com/impact/index.php/jpk, 2025)
Learning Al-Qur'an with the Qurani method at Lembaga Pemasyarakatan (Lapas) Narcotics Pakem Yogyakarta aims to improve the ability to read Al-Qur'an inmates as well as shaping their religious character. The Qurani method is designed to facilitate learning the Qur'an through systematic stages, namely letter recognition, pronunciation, changes, and recitation practice. This study evaluates the implementation, challenges, and success of the programme through a service learning approach for 12 months. The evaluation results showed significant improvement in Qur'an recitation skills as well as internalisation of religious values among participants. This article proposes recommendations for the development of similar programmes in other institutions.